(untitled) (Hungarian Journal of Industry and Chemistry, 2011)
This study investigates the effect of multi-walled carbon nanotube (MWCNT) content on the dynamic mechanical properties and crystallinity of polypropylene (PP). Carbon nanotubes are promising additives for polymer composites due to their excellent mechanical, electrical, and thermal properties. Polypropylene/multi-walled carbon nanotube (PP/MWCNT) composites were produced in single and double screw extruders. The composites contained 0.5, 2, 3 and 5 wt% multi walled carbon nanotubes. The effect of MWCNT addition on the thermal transitions of the PP was investigated by differential scanning calorimetry (DSC) measurements. Dynamic mechanical analysis (DMA) studies revealed an enhancement of the storage modulus.